Countryinfo App Development to Facilitate Access to Android-Based Country Information - Thanel Richard Angwarmasse; Mariano Antonino Mingga Juluk; Muchamad Rachel Rafiola; Misni Misni (Journal Collabits, 2025)
In the era of globalization and technological advancement, the need for fast, accurate, and easily accessible information has significantly increased. The CountryInfo App was developed as an innovative solution to simplify access to real-time country information. This application offers two main features: searching for country details by name and a randomizer feature for exploring country data interactively. Utilizing technologies such as Kotlin for user interface development, Flask for backend management, and public APIs for retrieving real-time data in JSON format, the application is designed to provide users with an intuitive and interactive experience. Testing results demonstrate a responsive performance, with an average access time of less than 2 seconds. This study aims to provide practical benefits to society in education, research, and personal needs while serving as a case study for API technology implementation in mobile application development.